(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, repesentatives of the Mangit dynasty, who ruled the state power in Bukhara from the middle of the 18th century to the beginning of the 20the century, the system of state administration, the internal and external policy of the state, relations with neighboring countries, the social and economic condition of the people, taxes, trade and embassy relations are studied and relevant conclusions are given.